Avaliação da qualidade de vida dos servidores da segurança pública do estado de Goiás - Ikegami , Tereza Yoshie (2014)
The purpose of this study was to assess QOL (quality of life) of workers of Board of Public Security and Justice of the State of Goias, Brazil, and to identify the socio-demographic and occupational variables that may influence their QOL. This is an epidemiological cross-sectional study, conducted in the metropolitan region and countryside municipalities of the state. The institutions studied were the Military Police (MP), the Firefighting Brigade (FB), the Civilian Police (CP) and the Technical and Scientific Police (TSP). Data were collected using the World Health Organization Quality of Life Instrument Bref (Whoqol-bref) and a questionnaire with socio-demographic and occupational variables of interest. Data analysis was conducted using the Statistical Package for Social Sciences (SPSS), version 18.0. Descriptive statistics and measures of central tendency were calculated for the variables of interest. To evaluate the association between explanatory variables and the QOL scores (and their domains), the non-parametric Mann-Whitney and Kruskal-Wallis tests were used with p<5%. Of 1.039 workers (356 of MP, 275 of FB, 188 of CP and 203 of TSP), 78.1% were male, the predominant age was 31-50 years old; 76.4% were married or in a stable relationship. Regarding length of working in public service, 57.3% had been working up to 15 years. Of the 1.039 respondents, 62.4% were in field work activities. The scores of overall QOL and of the physical, psychological and social domains were very good; as for the environmental domain, the scores were good. The following variables were statistically significant for a better QOL: being married, working at countryside municipalities, field work activities and exercising regularly. The following variables were associated with a worse QOL: being female and having a sick family member. Good scores of QOL means offering the minimum conditions for individuals to develop the maximum of their potential to live, feel, love, work and produce.